Factors Causing Early Marriage in Merauke District, Merauke Regency, South Papua Province - Yuwono Yoyo Restu Pramono; Faisal; Ade Yamin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Currently, the occurrence of early marriage cases is increasing rapidly and is rampant in Merauke Regency, in the assumption that there is an increase in cases of early marriage which is increasing every year which tends to be based on the influence of various factors including a prevalent culture that requires girls to marry as soon as they reach puberty. Second, unfavourable economic conditions which make early marriage a solution in reducing the economic burden. And third, the occurrence of violence and social pressure that occurs in a woman which makes them live in an insecure state so that they need a life companion to protect them. This research uses an empirical or field research method by collecting data in the field (field research) by promoting a qualitative approach (juridical sociological). In collecting the data obtained by relying on interviews with the perpetrators of early marriage. While the data analysis technique uses the stages of data reduction, presentation, and conclusion drawing to display the appropriate data. Based on the results of the study, it is found that through these factors, it shows that in essence what is seen in the purpose of early marriage is more based on the desire to solve problems in life that are far from the true purpose of a marriage is to build a family or household that is eternal and happy. So it can be concluded that early marriage actually still cannot be said to be a solution if it is based on these factors because on the other hand early marriage also has an impact on individuals, society and KUA agencies.